Distribution mapping of metal sediment using polarization data interpretation on the field “X” in PT Newmont Nusa Tenggara (PT NNT) - Sukri Arjuna; Adi Susilo; Sunaryo S (Department of Physics, Sebelas Maret University, 2016)
Geophysical research has been done on mapping distribution of metal deposits in the field